2010
DOI: 10.1179/136217109x12518083193432
|View full text |Cite
|
Sign up to set email alerts
|

Probing influence of welding current on weld quality in two wire tandem submerged arc welding of HSLA steel

Abstract: Two wire tandem submerged arc welding (SAW-T) involves application of two electrode wires to form a single weld pool with one wire leading the other along the weld interface. Realisation of the influences of the lead and trail wire currents on the weld bead morphology and the weld strength are important in SAW-T. The authors here present an experimental and computational investigation on SAW-T process. The concept of central composite rotatable design is followed for designing the experimental trials. The fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…A comparison 26) also observed that the leading and trailing arc currents have negative influence while the trailing wire negative pulse time and welding speed have positive influence on the acicular ferrite volume fraction and the weld mechanical properties. Similar trend of volume fractions were also observed in some other works (14,16,27,28). In typical tandem submerged arc welding of HSLA steel, welding speed from 9.0 to 11.5 mm/s, leading wire current from 530 to 580 A, and trailing wire negative current from 680 to 910 A are found to be the most suitable 29) .…”
Section: Experimental Studies 21 Variants Of Saw Processsupporting
confidence: 65%
“…A comparison 26) also observed that the leading and trailing arc currents have negative influence while the trailing wire negative pulse time and welding speed have positive influence on the acicular ferrite volume fraction and the weld mechanical properties. Similar trend of volume fractions were also observed in some other works (14,16,27,28). In typical tandem submerged arc welding of HSLA steel, welding speed from 9.0 to 11.5 mm/s, leading wire current from 530 to 580 A, and trailing wire negative current from 680 to 910 A are found to be the most suitable 29) .…”
Section: Experimental Studies 21 Variants Of Saw Processsupporting
confidence: 65%
“…Moreover, they showed that the heat source model parameters also depend upon welding parameters. Heat transfer and cooling rate of the fusion zone for SAW-T welding process were investigated using finite element methods by Kiran et al [17]. They showed that welding cooling rates decreases with higher welding current.…”
Section: Introductionmentioning
confidence: 99%
“…Several numerical [5][6][7][8][9][10][11][12][13][14][15][16][17] and experimental investigations [1,2,[18][19][20][21][22] of arc welding have been reported by various researchers. Rosenthal [23] first proposed a mathematical model of a moving heat source under the assumption of quasi-steady state; however, as many researchers have discussed, Rosenthal's analysis (that assumes either a point, line, or plane source of heat) has major error for temperatures in or near the fusion and heat-affected zones [24].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13]18) The conduction heat transfer based models for GMAW and SAW processes have also remained an effective recourse because of their computational simplicity, flexibility to consider wide-ranging weld joint geometry, and quick adoptability in several numerical analysis software that are widely available. [5][6][7][14][15][16][17] In contrast, the analytical heat transfer models to simulate GMAW process could consider simple joint geometry and constant material properties that usually inhibited accurate prediction of temperature field within the weld pool. 19,20) The majority of the conduction heat transfer based numerical models considered a volumetric heat source to account for the transfer of arc energy in the weld pool and, the heat source dimensions are determined either arbitrarily or based on the measured final weld dimensions that had restricted the predictive capability of these models.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Although several efforts are published to simulate autogenous fusion welding processes, similar models that can also consider the electrode deposition such as in gas metal arc welding process (GMAW) and submerged arc welding (SAW) are only a few. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] The convective heat transport based have remained as a route to realize heat transfer and fluid flow in weld pool, and the resulting weld pool profile. [8][9][10][11][12][13]18) The conduction heat transfer based models for GMAW and SAW processes have also remained an effective recourse because of their computational simplicity, flexibility to consider wide-ranging weld joint geometry, and quick adoptability in several numerical analysis software that are widely available.…”
Section: Introductionmentioning
confidence: 99%